Leading international models and patterns in the use of renewable energies - Ahmed Ali Owainy (African Journal of Advanced Pure and Applied Sciences, 2025)
This study covers policies and leading experiences around the world for international renewable energy models and approaches. The most prominent of these models is the German model (Energiewende), which aims for a comprehensive transition from fossil fuels and nuclear power to renewable energy. German policy focused on providing significant financial support for these projects through feed-in tariffs and local community participation in energy projects. More than 40% of electricity generated from renewable sources (2023) and the development of a national solar and wind energy industry. The Danish model focused on wind energy, with features including more than 50% of electricity generated from wind power, smart grids and advanced storage, and strong community participation in wind projects. The strategy pursued in the Chinese model was to be an industrial leader in renewable energy technology production, and policies supported local manufacturing of solar energy and batteries. Clear objectives were included in five-year plans. Results: China is the largest producer and user of solar and wind energy globally. Huge investments in super grids. The Moroccan model focused on solar and wind energy. The Noor Solar Energy Project: one of the largest in the world. National strategy: achieving 52% of electricity from renewable sources by 2030. The Indian model: Motivation: Energy demand and air pollution. Policies: Mega-solar energy projects (e.g., Rewa). Support for financing and infrastructure. Goals: 500 gigawatts of renewable energy by 2030.